Anisogomphus yingsaki (Odonata: Gomphidae) sp. nov., a new gomphid species from Thailand - Makbun, Noppadon (Zootaxa, 2017)
Anisogomphus yingsaki sp. nov. (holotype male: Ban Na Kha, Ban Muang, Sakon Nakhon province, Thailand, altitude 170–175 m, 22-vi-2016) is described and illustrated. The new species is most similar to A. bivittatus from India and Nepal, and also A. flavifacies, and A. resortus from China in the shape of anal appendages. However, it can be separated from all of these by a combination of the following characters: shape of antehumeral stripes, abdominal pattern, shape of vesica spermalis and female valvula vulvae. The behavior of the new species, including crepuscular activity, is briefly discussed.